Inter-site comparability of 4D flow cardiovascular magnetic resonance measurements in healthy traveling volunteers—a multi-site and multi-magnetic field strength study - Müller, Maximilian; Daud, Elias; Langer, Georg; Gröschel, Jan; Viezzer, Darian; Hadler, Thomas; Jin, Ning; Giese, Daniel; Schmitter, Sebastian; Schulz-Menger, Jeanette; Trauzeddel, Ralf F. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundTime-resolved 3D cine phase-contrast cardiovascular magnetic resonance (4D flow CMR) enables the characterization of blood flow using basic and advanced hemodynamic parameters. However, different confounders, e.g., different field strength, scanner configurations, or sequences, might impact 4D flow CMR measurements. This study aimed to analyze the inter-site reproducibility of 4D flow CMR to determine the influence of said confounders.MethodsA cohort of 19 healthy traveling volunteers underwent 4D flow CMR at four different sites (Sites I–III: 3 T scanner; Site IV: 1.5 T scanner; all Siemens Healthineers, Erlangen, Germany). Two protocols of one 4D flow CMR research sequence were performed, one acquiring velocity vector fields in the thoracic aorta only and one in the entire heart and thoracic aorta combined. Basic and advanced hemodynamic parameters, i.e., forward flow volume (FFV), peak and mean velocities (Vp and Vm), and wall shear stress (3D WSS), at nine different planes across the thoracic aorta (P1–P2 ascending aorta, P3–P5 aortic arch, P6–P9 descending aorta) were analyzed. Based on a second scan at Site I, mean values and tolerance ranges (TOL) were generated for inter-site comparison. Equivalency was assumed when confidence intervals of Sites II–IV lay within such TOL. Additionally, inter- and intra-observer analysis as well as a comparison between the two protocols was performed, using an intraclass correlation coefficient (ICC).ResultsInter-site comparability showed equivalency in P1 and P2 for FFV, Vp, and Vm at all sites. Non-equivalency was present in various planes of P3–P9 and in P2 for 3D WSS in one protocol. In total, Site IV showed the most disagreements. Protocol comparison yielded excellent (>0.9) ICC in every plane for FFV, good (0.75–0.9) to excellent ICC for Vm and 3D WSS, good to excellent ICC in eight planes for Vp, and moderate (0.5–0.75) ICC in one plane for Vp. Inter- and intra-observer analysis showed excellent agreement for every parameter.ConclusionsBasic and advanced hemodynamic parameters revealed equivalency at different sites and field strength in the ascending aorta, a clinically important region of interest, under a highly controlled environment.